PENGARUH STRATEGI PEMBELAJARAN RECIPROCAL TEACHING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV MI NIDHOMIYAH JOMBANG - Faridatul Masruroh; Tomi Syafrudin (Jurnal Prinsip Pendidikan Matematika, 2019)
Selection of appropriate learning strategies by teachers tailored to the subject matter, so that students can understand the subject clearly. Reciprocal Teaching is a learning strategy so that learning objectives are reached quickly through the process of independent learning. By presentation in front of a class, students are expected to achieve learning objectives and increase learning independence. This study aims to determine whether there is an influence of Reciprocal Teaching towards mathematics learning outcomes of fourth-grade students MI Nidhomiyah Jombang academic year 2018/2019. The calculation of the t-value uses SPSS 16. The result of t-value is 4,667 with sig (2 tailed)= 0,000. The data result showed that is rejected. The researchers concluded that there is influence Reciprocal Teaching towards mathematics learning outcomes.